Implicit Theories of Intelligence and Corrective Feedback Preferences - HosseiniZade Samane Saddat; Ali Mohammad Fazilatfar; Ali Akbar Jabbari; Mohammad Javad Rezai (Iranian Journal of Applied Language Studies, 2022)
Considering the facilitative role of corrective feedback in language learning, the impact of learners’ noticing on its effectiveness, and the significant contributions of individual attributes in learners’ noticing the corrective feedback, this study is designed to examine how learners’ implicit theories of intelligence (Mindset), an individual attribute, predict their preferences for oral corrective feedback (henceforth, OCF). A total of 143 Iranian EFL learners participated in the study. The participants were assigned to groups of fixed mindset (N=26) and growth mindset (N=26) based on their scores on Language Mindset Inventory (LMI) scale. The data obtained from the questionnaires were analyzed quantitatively. The results indicated that there were significant differences between the fixed-mindset and the growth-mindset groups in their beliefs toward some aspects of OCF. All in all, it can be claimed that language mindset (henceforth, LM) has a significant role in EFL learners’ beliefs about OCF. Pedagogical implications for considering learners’ LM in providing OCF are also discussed.